2017
DOI: 10.3310/pgfar05190
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic coagulopathy and massive transfusion: improving outcomes and saving blood

Abstract: Introduction Dysfunction of the coagulation system, termed trauma-induced coagulopathy (TIC), is a major problem in patients who bleed after injury. Trauma haemorrhage is considered one of the leading preventable causes of death worldwide. Deaths occur early and, despite the presence of trauma teams and large transfusions of blood products, outcomes remain poor. Methods We conducted a multimodal programme of work to develop o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 34 publications
1
30
0
4
Order By: Relevance
“…Davenport et al demonstrated that acute traumatic coagulopathy (ATC) is functionally characterized by a reduction in ROTEM clot firmness amplitude [20,36,[158][159][160]. With a cutoff value of A5 EX ≤ 35 mm, ROTEM can identify ATC at 5 min after CT and predict the need for massive transfusion (detection rate for A5 EX ≤ 35 mm, 71% vs. 43% for INR > 1.2; P < 0.001).…”
Section: In Trauma and Orthopedic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Davenport et al demonstrated that acute traumatic coagulopathy (ATC) is functionally characterized by a reduction in ROTEM clot firmness amplitude [20,36,[158][159][160]. With a cutoff value of A5 EX ≤ 35 mm, ROTEM can identify ATC at 5 min after CT and predict the need for massive transfusion (detection rate for A5 EX ≤ 35 mm, 71% vs. 43% for INR > 1.2; P < 0.001).…”
Section: In Trauma and Orthopedic Surgerymentioning
confidence: 99%
“…ROTEM-guided bleeding management algorithms have been shown to be effective in reducing transfusion requirements, health care costs, and complication rates. Several randomized clinical trials (RCTs), meta-analyses, and health technology assessments provided evidence that using ROTEM-guided algorithms in bleeding patients resulted in improved patient's safety and outcomes including perioperative morbidity and mortality [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Crew resource management has been shown to reduce mortality compared with non‐CRM institutions. In a national study in the UK with facilities that do not have CRM protocols, blood component therapy delivery was inconsistent and below recommended thresholds . At Penn Medicine Lancaster General Health, a study was undertaken to assess opportunity for improvement of their MTP.…”
Section: Methodsmentioning
confidence: 99%
“…The hope is that death can sometimes be pre‐empted by interrupting this lethal triad before the cycle becomes irreversible. It is notable that most deaths associated with MTP to treat coagulopathy occur within the first 6 h of trauma . Another group has found a fourfold increase in mortality when coagulopathy is present …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation